Whales, seals, fish, and man proceedings of the International Symposium on the Biology of Marine Mammals in the North East Atlantic, Troms", Norway, 29 November-1 December 1994 - International Symposium on the Biology of Marine Mammals in the North East Atlantic (1994 : Troms, Norway); Blix, Arnoldus Schytte; Walloe, Lars.; Ulltang, Oyvind (Amsterdam ; New York : Elsevier, 1995)
This volume outlines the major findings from the Norwegian research programme on whales and seals in Norwegian waters. A wide range of topics are covered, including physiological aspects, social organization, population dynamics, stock assessment and management. The book will be of great value to scientists and managers, as well as to members of the general public interested in environmental issues.
Περιέχει βιβλιογραφία και ευρετήριο.
Ηλεκτρονικό βιβλίο
Keywords: Marine mammals -- North Atlantic Ocean -- Congresses; Fisheries -- North Atlantic Ocean -- Congresses; Electronic books